NURSING KNOWLEDGE AND PRACTICE REGARDING THE PREVENTION OF PRESSURE ULCER - AIMAN, UE; SADDIQUE, H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Pressure ulcers are a significant concern in healthcare settings, particularly patients with limited mobility. Nurses play a critical role in preventing pressure ulcers through early identification and intervention. However, the effectiveness of preventive measures largely depends on nurses’ knowledge and practices regarding pressure ulcer prevention. Objective: This study aimed to assess the knowledge and practices of nurses working in tertiary care hospitals in Pakistan regarding the prevention of pressure ulcers. Methods: A descriptive cross-sectional study was conducted among 129 nurses at Jinnah Hospital, Lahore. Data were collected using a structured questionnaire that included demographic variables, knowledge, and practice sections related to pressure ulcer prevention. Descriptive statistics were used to summarise the data, and inferential statistics were applied to analyse the associations between knowledge, practices, and demographic variables. Results: Most participants were female (86.8%) and between the ages of 26 and 30 (55.0%). Most nurses had 1-3 years of experience (79.8%), and 38% held a Bachelor of Science in Nursing. While 62.8% of the nurses correctly identified that pressure ulcers result from unrelieved pressure for more than three hours, only 42.6% consistently used a risk assessment scale for pressure ulcer prevention. Significant gaps in knowledge and practice were observed, particularly regarding implementing prevention strategies. Conclusion: The findings indicate that while nurses in tertiary care hospitals in Pakistan have a basic understanding of pressure ulcer prevention, there is a need for continuous education and training programs to improve their practical application of preventive measures. Targeted interventions, particularly in high-risk departments such as medical and ICU units, could significantly reduce the incidence of pressure ulcers in hospitalised patients.